2020
DOI: 10.15414/jmbfs.2020.9.6.1204-1210
|View full text |Cite
|
Sign up to set email alerts
|

A BIOPROCESS DEVELOPMENT STUDY OF POLYPHENOL PROFILE, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF KOMBUCHA ENRICHED WITH Psidium guajava L.

Abstract: Acetobacter aceti, Acetobacter pasteurianus, Gluconobacter oxydans, and yeasts mostly Saccharomyces sp., Zygosaccharomyces kombuchaensis, Torulopsis sp., Pichia membranaefaciens, Brettanomyces sp. (Borkani et al., 2016). The main component of Kombucha tea is the light cellulose pellicle layer and the sour liquid broth (Goh et al., 2012). The microbes accumulate forming a firm cellulosic biofilm in the liquid-air interface during fermentation. which may act as a public good providing protection from invaders, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
11
0
6
Order By: Relevance
“…The antifungal and antibacterial activities may be due to the presence of the metabolites, polyphenols, and flavonoids. These results were supported by a detailed HPLC analysis of the kombucha's broth, showing that the gallic acid, catechin, guaiacol and coumaric acid were identified as the major bioactives [105].…”
Section: Kombuchamentioning
confidence: 59%
See 1 more Smart Citation
“…The antifungal and antibacterial activities may be due to the presence of the metabolites, polyphenols, and flavonoids. These results were supported by a detailed HPLC analysis of the kombucha's broth, showing that the gallic acid, catechin, guaiacol and coumaric acid were identified as the major bioactives [105].…”
Section: Kombuchamentioning
confidence: 59%
“…Fresh and ripen soursop (Annona muricata L.) fruits High potential to improve the quality, metabolites content, biological activity, and the Halal status of soursop kombucha [103] Black tea + sugar Invertase in kombucha tea increase the nutritional value of fermented product for diabetes patients [104] Green/black tea + guava juice Antimicrobial activity against human pathogenic bacterial strains and pathogenic fungi [105] Lactose and lactose-free milk Due to active microflora and organic acids, have a confirmed positive effect on the human body [106] Jujube kernel Obtaining of functional beverages and jujuboside B [107] Unbleached wheat flour Encapsulated kombucha-like sourdough starter for production of functional sourdough bread with extended shelf life and improved quality [108] Back tea with total replacement or in combination with Melissa officinalis, Quercus robur, Vaccinium myrtillus, Callisia fragrans Ascorbic acid and rutin obtaining [109] Probiotic bacteria from milk kefir grains use the carbon-and nitrogen-based nutrients within the fermentation medium and produce metabolites such as organic acids or carbonyl compounds and esters. In this way, products with specific taste and aroma are obtained.…”
Section: Kombuchamentioning
confidence: 99%
“…Singh et al (2019) reported that UV radiation-mediated decrements in Chl pigment contents, photosynthesis-evolving activity, enzyme activity, and PS II photochemistry were the major causes of retardation in the growth characters, as has been reported by the present work. It has been reported that UV radiation-mediated reduction in photosynthetic pigments was attributed to the inhibition of chlorophyll biosynthesis pathway-related enzymes and their precursors such as protochlorophyllide and disorientation of thylakoid membranes (Akladious and Mohamed 2017;Alharbi et al 2021;Khaleil et al 2020;Ranjbarfordoei et al 2011;Sharaf et al 2009). The results conform to the findings of Wang et al (2010), stating that UV radiation mediated a decrease in Chl and Car contents of Wolffia arrhiza.…”
Section: Discussionmentioning
confidence: 99%
“…Pada tabel 1 menunjukkan bahwa kombucha bunga telang pada perlakuan konsentrasi gula 20 dan 30% membentuk zona bening pada sekeliling sumuran baik pada bakteri gram positif maupun bakteri gram negatif dan hal tersebut mengindikasikan bahwa kombucha memiliki aktivitas sebagai antibakteri yang berpotensi dalam mencegah pertumbuhan keempat bakteri uji. Hasil penelitian ini diperkuat dengan terbentuknya zona hambat berupa zona bening pada kontrol positif berupa kombucha yang berbahan dasar teh hitam dan bersifat sebagai antibakteri (Khaleil et al, 2020). Kemampuan kombucha bunga telang mempunyai aktivitas sebagai antibakteri dalam spektrum yang sangat luas.…”
Section: Penentuan Zona Bening Berdasarkan Perhitungan Diameter Zona ...unclassified